PENGEMBANGAN MODEL PENDEKATAN PARTISIPATIF DALAM MEMBERDAYAKAN MASYARAKAT KOTA MEDAN UNTUK MEMPERBAIKI TARAF HIDUP - Dewi Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Poverty and community empowerment lately become a strategic issue. The abundance of available resource anIndonesian soil,demanding to be developed utilazation.